Maize milling method affects growth and zinc status but not Provitamin A carotenoid bioefficacy in male Mongolian gerbils - Gannon, B. M.; Pixley, KV; Tanumihardjo, S. A. (Elsevier, 2017)
Background: Vitamin A (VA) and zinc deficiencies are prevalent. Maize is a common staple, and milling affects nutrient and nutrient-modifier profiles. Objective: We investigated the interaction of maize milling methods (i.e., whole grain compared with refined) in male Mongolian gerbils aged 29–35 d with conventionally bred provitamin A–biofortified (orange) or white maize on VA and zinc status. Methods: Study 1 (n = 67) was a 2 × 3 milling (whole compared with refined) by VA [no–vitamin A placebo group (VA−), orange, and VA-supplemented group (VA+)] design, with 4 wk of VA depletion followed by six 4-wk treatments (n = 10/treatment). Study 2 (n = 33) was a 2 × 2 milling-by-zinc [no-zinc placebo group (Zn−) compared with zinc-supplemented group (Zn+)] design, including 2 wk of VA depletion followed by four 3-wk treatments (n = 8–9/treatment). For study 1, positive and negative control groups were given supplemental VA at equimolar amounts to β-carotene equivalents consumed by the orange groups (74 ± 5 nmol/d) or placebo, respectively. For study 2, positive and negative control groups were given 152 μg Zn/d or placebo, respectively. Results: Milling significantly affected zinc concentration, providing 44–45% (whole grain) or 9–14% (refined) NRC requirements. In study 1, orange maize improved liver VA concentrations (mean ± SD: 0.28 ± 0.08 μmol/g) compared with the white maize groups (0.072 ± 0.054 μmol/g). Provitamin A bioefficacy was similar. In study 2, neither zinc nor milling influenced liver retinol. Refined Zn− gerbils weighed less than others by day 14 (46.6 ± 7.1 compared with 56.5 ± 3.5 g, respectively; P < 0.0001). Milling affected pancreas zinc concentrations (refined Zn−: 21.1 ± 1.8 μg Zn/g; whole Zn−: 32.5 ± 5.8 μg Zn/g). Conclusions: Whole-grain intake improved zinc and did not affect provitamin A bioefficacy. Other factors affected by milling (e.g., shelf life, preference, aflatoxin fractioning) need to be considered to maximize health.